(untitled) (Journal of Universal Science Research, 2025)
The topic of our thesis is “Evolution and functioning of French borrowings in the English vocabulary in the field of fashion”. Borrowings are one of the important components of vocabulary. Studying the etymology of words is a way to trace the formation of the English language, to understand which languages influenced it. In the XX-XXI centuries, the vocabulary of the English language is replenished by borrowings from other languages, in particular from French, which determines the relevance of this study.